2016
DOI: 10.1186/s12887-016-0666-y
|View full text |Cite
|
Sign up to set email alerts
|

Parenting approaches, family functionality, and internet addiction among Hong Kong adolescents

Abstract: BackgroundInternet addiction (IA) among adolescents has become a global health problem, and public awareness of it is increasing. Many IA risk factors relate to parents and the family environment. This study examined the relationship between IA and parenting approaches and family functionality.MethodsA cross-sectional study was conducted with 2021 secondary students to identify the prevalence of IA and to explore the association between adolescent IA and familial variables, including parents’ marital status, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
111
4
20

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(157 citation statements)
references
References 50 publications
(68 reference statements)
15
111
4
20
Order By: Relevance
“…This study showed that 21.6% of adolescents met criteria for PIU. Although the prevalence of PIU varied widely according to different instruments, this prevalence is comparable to that reported in previous studies, as Internet addiction is encountered in 10% to 30% of Korean adolescents (Mak et al, ) and is more prevalent in Korean rural areas than that in other rural Asian areas (Wu et al, ). Indeed, the present results suggest that PIU is not rare among rural adolescents in Korea, and this high prevalence is likely due to the popularity of computers and smartphones in rural areas.…”
Section: Discussionsupporting
confidence: 90%
“…This study showed that 21.6% of adolescents met criteria for PIU. Although the prevalence of PIU varied widely according to different instruments, this prevalence is comparable to that reported in previous studies, as Internet addiction is encountered in 10% to 30% of Korean adolescents (Mak et al, ) and is more prevalent in Korean rural areas than that in other rural Asian areas (Wu et al, ). Indeed, the present results suggest that PIU is not rare among rural adolescents in Korea, and this high prevalence is likely due to the popularity of computers and smartphones in rural areas.…”
Section: Discussionsupporting
confidence: 90%
“…The present study shows a statistical significant relation between IA and academic level where the intermediate school students were the highest internet users than secondary school students only in Saudi group and this result in corresponding with Sasmaz et al (2014) [52] and Wu et al (2016) [55] where the IA increased among the lowest level of secondary school compared to the highest level. The internet is considered as an indicator of social and educational class, in the present study the IA was higher in Saudi group rather than the Egyptian one, where the Saudi students 22% of their fathers had a postgraduates level of education compared to 3.6% in Egyptian one (see Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…8 Several studies indicate adolescents with IA were significantly more likely to have dysfunctional familial relationships. [10][11][12][13] This survey also found statistically significant difference between average users and possible addicts/internet addicts based on their Family Characteristics.…”
Section: Discussionmentioning
confidence: 90%